Orbital motion - Roy, A. E. (Archie E.), 1924-2012 (Taylor & Francis, 2005)
Including a chapter that provides a treatment of the Caledonian symmetrical n-body problem, this mathematically detailed book on classical celestial mechanics covers modern applied areas such as satellite dynamics. It also includes coverage that may meet the needs of those in aerospace engineering and planetary science.